Characterizing solution set of a nonconvex programming problem via its dual problems - Đỗ, Sang Kim (Trường Đại học Đà Lạt, 2014)
Using duality theory, we propose a new approach to charact erize solution set of a nonconvex optimization problem. Several characterizations of solution set of the problem are established via it s dual problems. Charact eriza tions of solution sets of some class of convexj'nonconvex optimization problems given in several papers before can be covered. Example is given. Mathematics Subject Classification. 90C46, 49N15.